Significance of post-pacing intervals shorter than tachycardia cycle length for successful catheter ablation of atypical flutter. Issue 4 (16th November 2020) - Dall'Aglio, Pietro Bernardo; Johner, Nicolas; Namdar, Mehdi; Shah, Dipen C
Abstract: Aims: During entrainment mapping of macro-reentrant tachycardias, the time difference (dPPI) between post-pacing interval (PPI) and tachycardia cycle length (TCL) is thought to be a function of the distance of the pacing site to the re-entry circuit and dPPI < 30 ms is considered within the re-entry circuit. This study assessed the importance of PPI < TCL as a successful target for atypical flutter ablation. Methods and results: A total of 177 ablation procedures were investigated. Surface electrocardiograms (ECGs) were evaluated and combined activation and entrainment mapping were performed to choose ablation sites. Each entrainment sequence immediately preceding static radiofrequency delivery at the same site was analysed. A total of 545 entrainment sequences were analysed. dPPI < 0 ms was observed in 45.3% (247/545) sequences. Ablation resulted in tachycardia termination more often at sites with dPPI < 0 (27.8% vs. 14.5%, P  < 0.001) and with a progressively increasingly inverse correlation between dPPI duration and ablation success [odds ratio (OR): 0.974; 95% confidence interval (CI) 0.960–0.988; P  < 0.001]. Tachycardia termination or cycle length prolongation also occurred more often at sites with dPPI < 0 (50.6% vs. 33.2%, P  < 0.001) and with a similar inverse correlation with dPPI duration (OR: 0.972; 95% CI 0.960–0.984; P  < 0.001). Twelve-lead synchronous isoelectric intervals were observed in 64.4% (163/253) flutter ECGs and were associated with a dPPI < 0 (75.3% vs. 55.8%, P  < 0.001). Conclusion: When combined with activation mapping, a negative dPPI is a more effective parameter for identifying a target for successful ablation compared to a dPPI = 0–30 ms. Its occurrence is associated with a critical small narrow slow-conducting isthmus at the target site.